2021
DOI: 10.3390/ijms222111633
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Folate Metabolism Is Selectively Cytotoxic to Glioma Stem Cells and Effectively Cooperates with Differentiation Therapy to Eliminate Tumor-Initiating Cells in Glioma Xenografts

Abstract: Glioblastoma (GBM) is one of the deadliest of all human cancers. Developing therapies targeting GBM cancer stem cells or glioma stem cells (GSCs), which are deemed responsible for the malignancy of GBM due to their therapy resistance and tumor-initiating capacity, is considered key to improving the dismal prognosis of GBM patients. In this study, we found that folate antagonists, such as methotrexate (MTX) and pemetrexed, are selectively cytotoxic to GSCs, but not to their differentiated counterparts, normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The human GSCs used in this study (GS-Y01, GS-Y03, and TGS01) were maintained under previously reported monolayer stem cell culture conditions [ 8 , 39 ]. The differentiation of GSCs was induced by culturing cells in a DMEM/F-12 medium supplemented with 10% fetal bovine serum (FBS), 100 units/mL of penicillin, and 100 μg/mL of streptomycin for 2 weeks [ 8 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The human GSCs used in this study (GS-Y01, GS-Y03, and TGS01) were maintained under previously reported monolayer stem cell culture conditions [ 8 , 39 ]. The differentiation of GSCs was induced by culturing cells in a DMEM/F-12 medium supplemented with 10% fetal bovine serum (FBS), 100 units/mL of penicillin, and 100 μg/mL of streptomycin for 2 weeks [ 8 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The human GSCs used in this study (GS-Y01, GS-Y03, and TGS01) were maintained under previously reported monolayer stem cell culture conditions [ 8 , 39 ]. The differentiation of GSCs was induced by culturing cells in a DMEM/F-12 medium supplemented with 10% fetal bovine serum (FBS), 100 units/mL of penicillin, and 100 μg/mL of streptomycin for 2 weeks [ 8 , 39 ]. IMR90, a human normal fetal lung fibroblast cell line, was obtained from the American Type Culture Collection (Manassas, VA, USA) and maintained in DMEM supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations